Penerapan Media Smart Box Terhadap hasil Belajar Siswa Pada Mata Pelajaran IPAS Kelas IV SD Inpres Parangmalengu - Alfiana, Rahmadani; Irmawanty; Anisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze improvements in science learning outcomes through the implementation of Smart Box media among fourth-grade students at Parangmalengu Inpres Elementary School. This study was a pre-experimental study with a One Group Pretest-Posttest Design. The study was conducted at Parangmalengu Inpres Elementary School, with 24 fourth-grade students as subjects. The population in this study was all 24 fourth-grade students at Parangmalengu Inpres Elementary School. The sample also consisted of all 24 fourth-grade students at Parangmalengu Inpres Elementary School, using a saturated sampling technique. The data collection technique used was a learning outcome test in the form of a pretest and a posttest. The research instrument consisted of 25 multiple-choice student learning achievement tests, covering levels C1 (remembering), C2 (understanding), C3 (applying), and C4 (analyzing). The data analysis techniques used were descriptive statistical analysis and the N-Gain test. The results showed that the average pretest score was 56.00, which is in the low category, while the average posttest score increased to 93.00, which is in the high category. The N-Gain test results showed an average score of 0.82, or 82%, which is in the high category. This indicates that the use of Smart Box media is effective in improving student learning outcomes in the science subject of energy transformation in fourth-grade students at SD Inpres Parangmalengu.